Marten Subnivean Access Point Use: Response to Subnivean Prey Levels - Sherburne, S. S.; Bissonette, John A. (The Journal of Wildlife Management, 1994)
Because marten (Martes americana) require subnivean access for cover, prey access, and homeothermic reasons, we developed a predictive model to explain their differential use of subnivean access holes in Yellowstone National Park. We included prey biomass and percent ground cover of coarse woody debris (CWD) as explanatory variables in a logistic regression model because of their biological importance to marten in winter. Taken singly, relative prey biomass yielded the best univariate predictive model (P = 0.001). However, we included CWD in a multivariate model because of its biological significance. Coarse woody debris provides structure that intercepts snowfall, creating subnivean tunnels, interstitial spaces, and access holes, and was found at used and unused access points. Mean prey biomass was 205.4 g/400 m2 (SE = 20.26) and 108.2 g/400 m2 (SE = 10.73) at used and unused points (P < 0.001), respectively, while mean percent ground cover of CWD was 24.7 (SE = 2.30) and 18.5% (SE = 1.18) at used and unused access points (P = 0.017), respectively. As CWD increased by 5%, the probability of use by marten increased 1.12 times, and for every 50 g increase in relative prey biomass, marten were 1.37 times more likely to use that access point. Prey biomass varied (P < 0.001) among subnivean access points, and marten chose between different access points primarily on the basis of prey abundance levels. Older growth forests with accumulated CWD will enable marten to forage effectively in winter.